N-Cadherin Promotes Recruitment and Migration of Neural Progenitor Cells from the SVZ Neural Stem Cell Niche into Demyelinated Lesions - Klingener, Michael (Society for Neuroscience, 2014)
Discrete cellular microenvironments regulate stem cell pools and their development, as well as function in maintaining tissue homeostasis. Although the signaling elements modulating neural progenitor cells (NPCs) of the adult subventricular zone (SVZ) niche are fairly well understood, the pathways activated following injury and the resulting outcomes, are less clear. In the present study, we used mouse models of demyelination and proteomics analysis to identify molecular cues present in the adult SVZ niche during injury, and analyzed their role on NPCs in the context of promoting myelin repair. Proteomic analysis of SVZ tissue from mice with experimental demyelination identified several proteins that are known to play roles in NPC proliferation, adhesion, and migration. Among the proteins found to be upregulated were members of the N-cadherin signaling pathway. During the onset of demyelination in the subcortical white matter (SCWM), activation of epidermal growth factor receptor (EGFR) signaling in SVZ NPCs stimulates the interaction between N-cadherin and ADAM10. Upon cleavage and activation of N-cadherin signaling by ADAM10, NPCs undergo cytoskeletal rearrangement and polarization, leading to enhanced migration out of the SVZ into demyelinated lesions of the SCWM. Genetically disrupting either EGFR signaling or ADAM10 inhibits this pathway, preventing N-cadherin regulated NPC polarization and migration. Additionally, in vivo experiments using N-cadherin gain- and loss-of-function approaches demonstrated that N-cadherin enhances the recruitment of SVZ NPCs into demyelinated lesions. Our data revealed that EGFR-dependent N-cadherin signaling physically initiated by ADAM10 cleavage is the response of the SVZ niche to promote repair of the injured brain.